Menerapkan Public Speaking pada Siswa Sekolah Dasar Katolik Lewopenotung di Desa Lusiduawutun Kecamatan Nagawutung Kabupaten Lembata - Yosefina M.I. Amung; Yosep Riang; Mikhael Rajamuda Bataona (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The program of Implementation of public speaking in Lewopenotung Catholic elementary school students in Lusiduawutun village, Nagawutung sub-district, Lembata regency Aims to strengthen the basic framework for efforts to realize inner and outer well-being, encouraging and motivating the potential of community human resources at KKN locations towards a dynamic life, having sufficient religious insight, a high and democratic work ethic. This research uses a qualitative approach with descriptive methods. Data collection was carried out through direct observation, interviews with related parties such as village heads, staff and the community as well as documentation regarding facilities and infrastructure as well as biographical data in Lusiduawutun village. The results of the research show that this program is very successful and can help Lewopenotung Catholic elementary school students train themselves to be able to speak in front of many people.